ISLAMIC EDUCATION MANAGEMENT STRATEGY IN OPTIMIZING THE ROLE OF PEER COUNSELORS TO PREVENT CYBERBULLYING - Frendi Fernando; Sri Mulyani; Lastri Khasanah; Fibriana Miftahus Sa'adah; Noneng Siti Rosidah; Lia Nur Khotijah (Program Studi Manajemen Pendidikan Islam, 2026)
The phenomenon of cyberbullying in Islamic education environments has become increasingly concerning due to the rapid digitalization among young students. Islamic education management must not only focus on cognitive aspects but also protect students' mental health from the threat of digital aggression. This study aims to examine the role of peer counselors in preventing cyberbullying in madrasas through a management approach based on Islamic counseling. Using a mixed-methods approach, this research collects both quantitative and qualitative data to evaluate the effectiveness of the peer counselor role and the managerial strategies implemented. The results show that the role of peer counselors, trained with noble character values and digital literacy, is effective in reducing cyberbullying cases by 43%. This approach proves to be more adaptive compared to traditional counseling methods, given the intense interactions among students and shared communication language. The study suggests the importance of a more organized managerial structure in empowering peer counselors to create a safe and ethically sound digital ecosystem in Islamic educational settings